The African Union Great Green Wall Initiative Strategy (2024-2034): A new continental roadmap for restoration, sustainable land management and climate resilient livelihoods - Trautman, Sabrina; Chevallier, Romy; Gosling, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This infonote provides a brief overview of the African Union Great Green Wall Initiative (GGWI) Strategy (2024-2034). It explains why and how the GGWI Strategy was updated, highlighting the involvement of AICCRA experts. It provides the new Strategy's strategic framework and its guiding principles, and describes the four strategic intervention axes. It highlights the Strategy's emphasis on climate change and how climate-smart agriculture is recognised as a key approach for land restoration and resilience building. It reflects on the processes and timeline towards the formal adoption of the new GGWI Strategy including the suggested key activities for the first year of implementation. The infonote concludes with reflections from the AICCRA experts who were engaged in the participatory development process of the Strategy.